Increasing exposure to the UV filters octocrylene and 2-ethylhexyl salicylate in Germany from 1996 to 2020: Human biomonitoring in 24-h urine samples of the German Environmental Specimen Bank (ESB) - Daniel Bury; Till Weber; Katharina E. Ebert; Stephanie Zülz; Thomas Brüning; Holger M. Koch; Marike Kolossa-Gehring (Environment International, 2023)
The UV filters octocrylene (OC) and 2-ethylhexyl salicylate (EHS) are commonly used in sunscreens and frequently detected in environmental media. However, knowledge on human exposures is scarce.In this human biomonitoring (HBM) study, we analyzed concentrations of exposure biomarkers specific to OC (CPAA, DOCCA, 5OH-OC) and EHS (5OH-EHS, 5oxo-EHS, 5cx-EPS) in 24-h urine samples (n = 420) from the German Environmental Specimen Bank (ESB). These samples were collected from German students (20–29 years; 30 males/30 females per year) between 1996 and 2020 (4-year intervals; collection in winter).We found continuously increasing OC and EHS exposures (Jonckheere-Terpstra; p < 0.001) documented by very few to no samples with concentrations of the most sensitive biomarkers CPAA and 5cx-EPS above the limit of quantification (LOQ) in 1996 (5 % and 0 %, respectively) and reaching 100 % and 93 % above the LOQ in 2016, with median concentrations of 4.79 and 0.071 µg/L, respectively. In 2020, biomarker concentrations slightly decreased to 3.12 µg/L CPAA (97 %>LOQ) and 0.060 µg/L 5cx-EPS (88 %>LOQ). This general trend was confirmed by the other biomarkers, however at lower detection rates. Based on metabolite excretion in the 24-h urine samples and human toxicokinetic data, we calculated maximum daily intakes (DI) of 17 µg/(kg bw * d) OC and 59 µg/(kg bw * d) EHS. Based on a derived no-effect level (DNEL) of 0.8 mg/(kg bw * d), the OC exposures of individuals in our study did not indicate any health risk. Similarly, for EHS all biomarker concentrations were well below the HBM-I values of 12 µg/L 5OH-EHS and 11 µg/L 5cx-EPS.Our data proves the general applicability of specific OC and EHS metabolites for HBM in the general population and shows clearly increasing exposures. Higher (co-)exposures must be expected in populations with increased sunscreen use such as (summer) vacationers, children and outdoor workers.